Psychometric Properties and a Preliminary Validation Study of the Italian Brief Version of the Communication Styles Inventory (CSI-B/I) - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania; Grambone, Angela (Frontiers in Psychology, 2020)
People will typically develop a communication style that tends to be coherent with their own fundamental personality traits. The current debate on communication style acknowledges the construct of adaptive behavior as an appropriate area where to include both the strictly personal aspects and social learning and cultural assimilation, which translate into communicative style as a specific form of adaptation integrating the behavioral and personality perspectives. Due to the lack of instruments in the Italian psychometric scenario to assess communication styles, the present study included the translation and validation of the Italian short version of the Communication Styles Inventory (CSI-B/I). Methods. The CSI-B/I was administered to a sample of 1,044 participants, while the concurrent validity was tested through a second administration to 518 participants along with the MPP (Multidimensional Personality Profile). Results. Confirmatory factor analysis bore out a three-factor solution (including 18 items) with good indices of adaptation to data, e.g., χ2/df = 1.251, RMSEA = 0.027, RMSEA 90% CI = 0.008–0.040, GFI = 0.958, AGFI = 0.937, CFI = 0.983 and NFI = 0.922. The CSI-B/I allows to measure three main dimensions of the communication style: impression manipulativeness; emotionality; expressiveness. Internal consistency reliability and significant correlations with the MPP supported the concurrent validity of the tool. Conclusion. By virtue of its good psychometric properties, CSI-B/I represents an important addition to the assessment in multiple contexts: companies, institutions, staff selection, individual and group profile analysis, coaching, psychotherapy, counseling, career guidance.